2021
DOI: 10.5194/ems2021-33
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drought assessment and the impacts on the agriculture and the forestry in Slovakia in 2020

Abstract: <p>Weather conditions were quite remarkable in Slovakia during the whole year of 2020. In terms of annual mean temperature, year 2020 was very warm, with temperature very much above normal and deviations ranging mostly from +1.3 to +1.6 ° C from the normal 1981-2010 (in mountain regions even more than +1.7 ° C). With the exception of spring 2020, all other seasons were significantly above normal in terms of seasonal temperature, especially the winter 2019/2020. From the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous study has confirmed that nutrients can increase the EO yield, as some are used to build many organic compounds, such as amino acids, proteins, enzymes, and nucleic acids. [25]…”
Section: Essential Oil Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study has confirmed that nutrients can increase the EO yield, as some are used to build many organic compounds, such as amino acids, proteins, enzymes, and nucleic acids. [25]…”
Section: Essential Oil Yieldmentioning
confidence: 99%
“…[24] Higher content of EOs in young needles could be related to the higher temperatures at the beginning of the year 2022, marking the period of needle growth and development. [25] In general, temperature is the most important environmental factor affecting the release of terpenes from aromatic plants, as the release of EOs is more active in hot weather. This may be related to the fact that the activity of most enzymes catalyzing the synthesis of VOCs is stimulated by temperature.…”
Section: Essential Oil Yieldmentioning
confidence: 99%